An Analysis of Figurative Language Used in Beowulf Poem Translated by Burton Raffel - Glen, Alexander; priyoto, priyoto; Lestari, Noviana (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
: Purpose of this study is to find the figurative language in Beowulf poem translated by Burton Raffel. The researcher read and studied Beowulf poem which were the subject of study. The poem itself composed in Old English consisting of 3,182 lines. Beowulf is an epic poem that consist seven six-line stanzas. The researcher use descriptive-qualitative method to collect the data. The language itself spoken in Anglo-Saxon England. Beowulf poem doesn’t rhyme not the same as most modern poem this day that have rhyme. But, to create unity and flow of language, poets like Beowulf instead used figurative language in their poetry. According to Perrine (in Arp, 2010: 73), figurative language refers to language that is not literary true but that is used to create truthful meaning and understanding. Kinds of figurative language that researcher found in this poem include, assonance, alliteration, kennings, similes, metaphors, imagery, caesura. stock and allusion. from the results of the study, it shows that the readers will be interested in knowing more about poetry and